Company report- paypal holdings,inc. industry and value drivers’ analysis - Ristivojevic, Sara (2021)
ThisreportpresentsanindustryanalysisaswellastheanalysisofthekeymajorvaluedriversforPayPal.Moreover, detailed analysis on the competition was conducted. The drivers such as E-commerce, Regulation, Research and Development expense and other have been identified. Finally, the relevant trends are analyzed for the purpose of forecast.